Plasma line studies in relation to Naturally Enhanced Ion Acoustic Lines (NEIALs) - Knutsen, Joachim Sveia (Universitetet i Tromsø, 2008)
New to the ESR common programmes is the inclusion of plasma lines along with the standard ion power density spectrum. Using data from the IPY common programme, a programme that has been run all through the International Polar Year, we have gone through large amounts of analysed data trying to find periods in time that fulfils the known criteria for finding Naturally Enhanced Ion Acoustic Lines (NEIALs), i.e. increased electron densities and penetration depth, a high electron temperature (>3000K) that is simultaneously equal to or greater than three times the ion temperature (Te>3Ti) and an increase in ion outflow velocities. Our primary focus has been on the parts of the year where conditions allow simultaneous runs of the Meridian Scanning Photometer (MSP) instrument over Svalbard, i.e. the dark winter months of December, January and February of 2007/2008. We get several results indicating field-aligned currents going both away and towards the radar simultaneously as well as several NEIALs occurring at altitudes that are normally considered to be too low with regards to some of the leading theories on the subject. Where such are observed, NEIALs are presented along with the corresponding plasma lines, as well as MSP plots, magnetometer data and the parameters of the solar wind taken by the ACE satellite to try and find more information regarding NEIALs and the underlying processes that cause them. A brief description of the leading theories regarding NEIALs is also included so we can argue whether or not our observations either strengthens or weakens these theories.